2013
DOI: 10.1016/j.pain.2013.08.026
|View full text |Cite
|
Sign up to set email alerts
|

Associations between KCNJ6 (GIRK2) gene polymorphisms and pain-related phenotypes

Abstract: Summary Variations in the KCNJ6 gene appear to influence both acute and chronic pain phenotypes. G-protein coupled inwardly rectifying potassium (GIRK) channels are effectors determining degree of analgesia experienced upon opioid receptor activation by endogenous and exogenous opioids. The impact of GIRK-related genetic variation on human pain responses has received little research attention. We used a tag SNP approach to comprehensively examine pain-related effects of KCNJ3 (GIRK1) and KCNJ6 (GIRK2) gene var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 48 publications
(99 reference statements)
2
35
0
Order By: Relevance
“…In contrast to the adult postoperative study with the combined Ϫ1250G/1032A haplotype (66 ), preterm infants with the Ϫ1250AA genotype who received either morphine or remifentanil needed more time to reach a pain-free state after endotracheal intubation (64 ). In an explorative analysis in 311 adult white patients undergoing total knee arthroplasty, both Ϫ1250GϾA and 1032AϾG were not associated with opioid dose (68 ). Of the 69 SNPs identified and analyzed in this study, significant hits were found with 8 other polymorphisms (rs1543754, rs858035, rs9981629, rs928723, rs2835925, rs2211843, rs1787337, rs2835930).…”
Section: Kcnj6mentioning
confidence: 66%
“…In contrast to the adult postoperative study with the combined Ϫ1250G/1032A haplotype (66 ), preterm infants with the Ϫ1250AA genotype who received either morphine or remifentanil needed more time to reach a pain-free state after endotracheal intubation (64 ). In an explorative analysis in 311 adult white patients undergoing total knee arthroplasty, both Ϫ1250GϾA and 1032AϾG were not associated with opioid dose (68 ). Of the 69 SNPs identified and analyzed in this study, significant hits were found with 8 other polymorphisms (rs1543754, rs858035, rs9981629, rs928723, rs2835925, rs2211843, rs1787337, rs2835930).…”
Section: Kcnj6mentioning
confidence: 66%
“…Moreover, Kir3 contribution to the clinical response of opioid analgesics has been confirmed in association studies showing that genetic variations of different Kir3 subunits influence opioid dose requirements for pain management (Lötsch et al, 2010;Bruehl et al, 2013). For DOPrs in particular, Kir3 contribution to peripheral (Chung et al, 2014) and spinal analgesia (Marker et al, 2005) has been clearly documented in preclinical models.…”
Section: D-opioid Receptors and Activation Of G Protein-coupled Inmentioning
confidence: 87%
“…One of these studies was conducted by our group (31), in which we sought to reveal the relationship between single-nucleotide polymorphisms (SNPs) in the KCNJ6 gene that encodes human GIRK2, especially within the exonic and 5′-flanking regions, and individual differences in opioid analgesic sensitivity. Another recent study found an association between KCNJ6 SNPs and pain-related phenotypes, reconfirming that the KCNJ6 gene is a promising target for investigating the genetic factors that contribute to pain and analgesia (29).…”
Section: Introductionmentioning
confidence: 75%
“…In these studies, the rs2835859 SNP was not investigated. In another recent study, Bruehl et al (29) revealed that eight KCNJ6 SNPs were significantly associated with the pain-related phenotype in Caucasian patients who underwent total knee arthroplasty (TKA) with postsurgical oral opioid analgesic medication (29). However, these SNPs and other SNPs reportedly tagged by these SNPs were not included in our candidate SNPs in the exploratory stage of the present study (Supplementary Table 4).…”
Section: Discussionmentioning
confidence: 94%